Socio-Political Tension in the Russian Society: Case Study of Youths of the Republic of Tatarstan - Efimova, Sabina Rafailevna; Khramova, Evgeniya Valerevna (Cuestiones Políticas, 2020)
This article explores the level of socio-political tension in Tatarstan. The object of the study is the youth social group as a bearer of social activism. The investigation methodology is based on conflict audit technology. Technology involves the use of markers to assess sociopolitical tensions. The main evaluation marker identified a request for social justice. The distinctive characteristics of youth groups are the discretion of group affiliation, the lack of formed ideological attitudes and the latent nature of the formation of the general ideology of various youth communities. The political activism of the Russian youth does not have a pronounced ideological character and is not a decisive factor in the formation of socio-political tensions. It is concluded that the interest in the study of young people who as a group lack common ideological positions is scientifically relevant, even within radicalized communities and with comparative political identities. Consequently, the presence of stable ideological positions will contribute, in principle, to the launching of internal integration processes in these communities and to a stable organization of their discourses and struggles.